DEVELOPING ECOLOGY AND ENVIRONMENTAL LEARNING MATERIALS BASED ON INTEGRATION CURRICULUM AND SCIENTIFIC LITERACY FOR NATIONAL PLUS SCHOOL STUDENTS IN INDONESIA - Silvia Sabatini; Binari Manurung; Mufti Sudibyo (Yayasan Seri Amal Medan, 2023)
The integration curriculum is a blend of the current national curriculum in Indonesia (Kurikulum 2013) and foreign curriculum from CIE (Cambridge International Examination). The problem is the unavailability of teaching materials is adequate for both curriculums simultaneously to be held. The aim of this study was to reveals the feasibility of learning material on ecology and environment topics based on integration curriculum and all the scientific literacy components. The feasibility of learning material is obtained through the validation by scientific literacy content experts, design experts, assessment from biology teachers and students’ responses. This research used Borg and Gall model which had 10 stages. However, this study is solely limited to preliminary field testing. Data validation was analyzed in descriptively qualitative. The research result showed that according to integration curriculum and scientific literacy by content experts, the feasibility of learning material was very feasible, in which the feasibility based on science as a body of knowledge has an average score 93.75%, whereas science as a way of investigation 88.54%, science as a way of thinking 87.5% and for interaction of science technology and society 86.25%. The feasibility of learning material’s design corresponded to the design expert was very feasible with 87.20% as well. Result of biology teacher assessment on learning material was 92.96% (very feasible). Students' response to the preliminary field individual testing was 83.92% (very feasible), small group testing was 78.56% (feasible) and large group testing was 80.84% (very feasible). The student's learning outcomes were increasing between experimental and control groups. The results of the unpaired t-test that have been obtained indicate that the significance value or Sig. (2 tailed) = 0,000 below 0.001. This indicates that there is a significant difference of using learning material for the ecology and environmental management topic based on integrated curriculum and scientific literacy to students’ learning outcomes of IGCSE 2 / grade X students, because Sig. (2 tailed) < 0.05